The influence of preterm premature rupture of membranes on maternal and neonatal outcome - Kornacki, Jakub; Goździewicz, Tomasz; Łabędzka, Izabela; Gruca-Stryjak, Karolina; Kornacka, Alicja; Skrzypczak, Jana; Szczapa, Jerzy (Archives of Medical Science, 2009)
Introduction: The aim of the study was to evaluate the influence of the interval between preterm premature rupture of membranes (PPROM) and delivery on maternal and neonatal complications in cases of PPROM occurring at different gestational ages. Material and methods: The study was conducted among 80 pregnant women with PPROM and their 85 newborns. Pregnant women were divided into two groups: 1) 46 patients with PPROM before 31 weeks gestation and 2) 34 women with PPROM at or after 31 weeks gestation. In each group, two subgroups of patients were formed: 1) patients with an interval between PPROM and delivery < 48 h and 2) patients with an interval between PPROM and delivery ł 48 h. Analysis of newborns concerned the frequency of various complications, including infections and complications of prematurity. Results: The frequency of almost all neonatal complications, including infections, was significantly higher in children delivered by mothers with PPROM before 31 weeks gestation than in babies of patients with PPROM at or after 31 weeks gestation. After taking the time between PPROM and delivery into account, there was a significant increase of neonatal sepsis and pneumonia only in newborns born ł 48 h after PPROM which occurred before 31 weeks gestation. Conclusions: The length of the interval between PPROM and delivery does not have a significant influence on the frequency of neonatal complications associated with prematurity but may slightly increase the risk of infection in newborns delivered after PPROM before 31 weeks gestation.